A smart switchable module for the detection of multiple ions via turn-on dual-optical readout and their cell imaging studies. Issue 19 (22nd April 2016) - Rai, Abhishek; Singh, Alok Kumar; Sonkar, Avinash Kumar; Prakash, Anand; Roy, Jagat Kumar; Nagarajan, Rajamani; Mishra, Lallan
Abstract : A rhodamine based switchable module, RHTH, displays multi-stimuli responses and logic gate based detection of Fe 3+, Hg 2+, CN − and S 2− ions at ppm levels together with the imaging of these cations in HeLa cell lines. Abstract : A module switchable as a function of multi-stimuli response has been designed. The module displays sequential logic gate-based detection of multiple ions (Fe 3+, Hg 2+, CN − and S 2− ) at ppm levels via a "turn on" signature which potentially meets real-world-challenges through a simple synthetic route, a fast response, water based-activity, naked-eye visualization, regenerative-action, high selectivity and multiple readout for precise analysis. Living cell imaging of Fe 3+ and Hg 2+ has also been carried out in HeLa cell lines.